Study of the Biological Activities of the Methanolic Extract of Globularia Alypum l from Algeria - Yahia Massinissa, Benhouda Afaf, Benbia Souhila, Loucif Lotfi, (Pakistan Journal of Medical & Health Sciences, 2022)
Medicinal plants are a very important therapeutic drug source in terms of medicinal use as they contain various secondary metabolites and bioactive compounds which procure to them several therapeutic potentials. The present research is aimed to study some biological activities of the methanol extract of Gloubular alypum maerial part , all the preliminary tests to be carried out for the quantitative metabolites determination of the used plant which have been confirmed the presence of many different concentration of flavonoids, polyphenols and flavanols and to evaluate different antioxidant activity busing two parameters DPPH and ferric potential FRAP and to test the inflammatory effect in vivo. The results obtained showed that the extract has an important antioxidant activity defined by 0,153. 0,116. 0,110(μg/ml). and significant anti-inflammatory activity.etalon at the following concentrations 0.23. 0.40. 0.34 (μg/ml). Gloubulariaalypum have significant therapeutic activities based on the present results obtained in current research and comparing to previous studiesso this what explain its utilization on alternative medicine and push us for anterior research.